Cost-effectiveness of 3d printing of anatomical models (VETERINARIA, 2021)
3D printing or additive manufacturing is one of the newest technologies that has begun to be used for production of anatomical models in veterinary medicine. The main aim of this research was to evaluate the total cost required for 3D printing of different anatomical models and the cost-effectiveness of use of these technologies in practice. For purpose of this study, we evaluated a cost of 3D printed model of the human heart, inner ear, cross-section of the animal cell and spinal cord, sheep, cow and cat brain and complete dog model with internal organs. The costs were calculated separately for raw material consumption and personnel operative work. The results show that 3D printing technologies are cost-effective for the production of anatomical models, and the total cost depends mostly on working time of the personnel.
Keywords: alternatives; costs; veterinary anatomy; 3D additive manufacturing